Design and Development of a Grid-Tied PV Inverter With GMPPT Technique and Reduced Number of Sensors - Pedro A. R. Freitas; Lucas P. Pires; Luiz C. Freitas; Gustavo B. Lima; Luiz C. G. Freitas (IEEE Access, 2022)
This paper presents the results of a study concerning the design and development of a grid-tied photovoltaic (PV) inverter with a new Global Maximum Power Point Tracking (GMPPT) technique. The main novelty presented concerns the development of a GMPPT strategy which is based on the principle of full scanning the output power curve (FS-AC-POWER GMPPT) and made possible to implement a highly efficient grid-tied PV inverter deploying only one voltage sensor and one current sensor. The presentation of the proposed technique, project and its control strategy are given a thorough and detailed description. The experimental results demonstrate that a high tracking factor (TF) is achieved (99.90%), with fast convergence speed even under partial shading conditions, while identifying false maximum power points (FMPP) and subsequent directing towards the GMPPT.